Flipped Classroom Approach in Dental Education: An Overview - Saravia-Rojas, Miguel Ángel (2023)
The flipped classroom is a pedagogical approach in which students are provided with videos, podcasts, and other resources to review in advance. This allows for a deeper understanding and clarification of the concepts during in-person or virtual activities. The flipped learning approach aims to bring about a change in the dynamics of teaching, promoting active learning within the classroom environment and placing the focus on the student. This document provides a review of the notable aspects of the flipped classroom and highlights its differences from the traditional lecture-based teaching method. Additionally, the impact of this approach in dentistry is examined, along with the challenges, commitments, and difficulties that may arise during its implementation.